2018
DOI: 10.1080/03019233.2018.1440160
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation model of fuel distribution in materials bed of iron ore sintering process

Abstract: In this study, the optimisation model of fuel distribution base on numerical simulation was proposed to reduce the fuel consumption of sintering process. The simulation model of sintering process was carried out according to the heat and mass transfer, and the physical and chemical reactions of sintering. Then the heat income and expenditure of solid mixture in different materials unit was analysed via the simulation model. And the fuel proportion was adjusted on the basis of the difference between total heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Sub-models, such as gas-solid chemical reaction rate models, gas homogeneous combustion reaction rate models, NO x reduction/formation models, gas-solid heat transfer model, melting and solidification models and sintering bed structure change model were presented in our previous work. 11) The gas-solid reactions include coke combustion, [12][13][14][15][16][17] limestone decomposition, 18,19) dolomite decomposition, 20) hematite reduction and magnetite oxidation. 21) To characterize the NO x behavior, four main NO formation/reduction mechanisms, 22) i.e., the fuel NO originating from coke particles, thermal NO formation, NO reductions by coke particles and CO are considered.…”
Section: Sub-modelsmentioning
confidence: 99%
“…Sub-models, such as gas-solid chemical reaction rate models, gas homogeneous combustion reaction rate models, NO x reduction/formation models, gas-solid heat transfer model, melting and solidification models and sintering bed structure change model were presented in our previous work. 11) The gas-solid reactions include coke combustion, [12][13][14][15][16][17] limestone decomposition, 18,19) dolomite decomposition, 20) hematite reduction and magnetite oxidation. 21) To characterize the NO x behavior, four main NO formation/reduction mechanisms, 22) i.e., the fuel NO originating from coke particles, thermal NO formation, NO reductions by coke particles and CO are considered.…”
Section: Sub-modelsmentioning
confidence: 99%
“…Obviously, only Test 4 realized relatively homogeneous thermal distribution, in association with automatic heat accumulation in the lower burden layer because of downward heat conduction in sintering [22]. It would contribute to high-quality sintering with lower TCC [23]. The results indicated that proper segregation of DP-4 was effective for improving indexes with relatively low sintering temperatures.…”
Section: Effect Of Segregation Of Pelletized Feed In the Burden Layermentioning
confidence: 99%
“…There is already technical support for fuel refinement utilization in a sintering plant in the form of a jaw crusher. Some scholars have studied the effect of fuel conditions on the thermal state by means of numerical models [9][10][11][12][13]. Won [14] studied the effect of fuel characteristics on the thermal state, Minerals 2023, 13, 511 2 of 14 demonstrating that the better the combustion characteristics, the faster the spread of the burning zone.…”
Section: Introductionmentioning
confidence: 99%
“…Huang [22] developed a heat balance equation for the sintering process to obtain a reasonable fuel distribution. Some scholars [11] proposed a reasonable fuel proportion for each unit of the material layer based on the maximum temperature. Others suggested a suitable particle size composition of the fuel through experiments.…”
Section: Introductionmentioning
confidence: 99%